Graphene-based two-dimensional mesoporous materials: Synthesis and electrochemical energy storage applications - Park, Jongyoon; Lee, Jiyun; Kim, Seongseop; Hwang, Jongkook (Materials, 2021)
Graphene (G)-based two dimensional (2D) mesoporous materials combine the advantages of G, ultrathin 2D morphology, and mesoporous structures, greatly contributing to the improvement of power and energy densities of energy storage devices. Despite considerable research progress made in the past decade, a complete overview of G-based 2D mesoporous materials has not yet been provided. In this review, we summarize the synthesis strategies for G-based 2D mesoporous materials and their applications in supercapacitors (SCs) and lithium-ion batteries (LIBs). The general aspect of synthesis procedures and underlying mechanisms are discussed in detail. The structural and compositional advantages of G-based 2D mesoporous materials as electrodes for SCs and LIBs are highlighted. We provide our perspective on the opportunities and challenges for development of G-based 2D mesoporous materials. Therefore, we believe that this review will offer fruitful guidance for fabricating G-based 2D mesoporous materials as well as the other types of 2D heterostructures for electrochemical energy storage applications.
Keywords: Electrochemical energy storage; General aspects; Mesoporous structures; Synthesis procedure; Synthesis strategy; Two Dimensional (2 D); Ultra-thin; Graphene; Lithium-ion batteries; Mesoporous materials; Supercapacitor; Two dimensional materials